Case report: Isolated eyelid metastasis of ccRCC 5 years after receiving radical nephrectomy - Yin, Huaqi; Du, Zheng; Zhang, Jiuwen; Ma, Yongkang; Zhao, Shiming; Yang, Tiejun (Frontiers in Oncology, 2024)
The most common sites of clear cell renal cell carcinoma(ccRCC) metastasis are the lung, bones, liver and brain; eyelid metastasis is a rare occurrence.We report a case of ccRCC metastasis to the left eyelid after radical nephrectomy, and remission after sunitinib treatment.Although the probability of eyelid metastasis rate is very low, tumor metastasis to the eyelid skin is possible after radical nephrectomy. Therefore, any rash like changes on the skin during the review procedure cannot be ignored by the physician. Nothing "Data Availability" statement The data that support the findings of this study are available from the corresponding author upon reasonable request.